VERBA LEMPAR BAHASA BALI: KAJIAN METABAHASA SEMANTIK ALAMI - Ariana, I Putu; Sulatra, I Komang (Sphota : Jurnal Linguistik dan Sastra, 2019)
Abstract   Throwing verbs in Balinese language have several lexicon variations which show differences in the meaning context. Different mentions depend on what is used to throw, the extent of the throw, the target of the throw, and the effects caused by the throw. This verb analysis is examined based on the Natural Semantics Metalanguage (NSM) approach which is a modern semantic study initiated by Wierzbicka (1996) which aims to describe the lexical, grammatical, and illocutionary meaning of a language. The results obtained that throwing verbs can be divided into two groups, namely based on the target throwing (nyabat, nyampar, nylampar, nylémpang, nimpug, and medut), and without target throwing (nguerang and ngentungang), verbs meaning 'throwing' in Balinese only has one prototype, that is, the prototype of action and this prototype also only has one default meaning type, namely the type of doing: thrown, and semantic verb structure which means 'throwing' in Balinese has a syntactic pattern NSM X does something at Y and Y thrown by X.   Keywords : throwing verbs, Balinese language, MSA